Why vaccines to HIV, HCV and Malaria have so far failed - Challenges to developing vaccines against immunoregulating pathogens - Magdalena Plebanski; Eric J. Gowans; Peter Smooker; Shuo Li (Frontiers Media SA, 2021)
Despite continuous progress in the development of anti-viral and anti-bacterial/parasite drugs, the high cost of medicines and the potential for re-infection, especially in high risk groups, suggest that protective vaccines to some of the most dangerous persistent infections are still highly desirable. There are no vaccines available for HIV, HCV and Malaria, and all attempts to make a broadly effective vaccine have failed so far. In this Research Topic we look into why vaccines have failed over the years, and what we have learn from these attempts. Rather than only showing positive results, this issue aims to reflect on failed efforts in vaccine development. Coming to understand our limitations will have theoretical and practical implications for the future development of vaccines to these major global disease burdens.